ETİK KODLARIN VEKÂLET MALİYETLERİ ÜZERİNDEKİ ETKİSİ İLE İLGİLİ BİR ARAŞTIRMA - (:unkn) unknown (My University, 2018)
Son 25-30 yıldır, siyasetten bilime, iş dünyasından medya dünyasına kadar hemen her alanda ahlaki davranış sorunları yaygınlaşmış, bu konu ile ilgili görüşler dile getirilmeye başlanmıştır. Bunun bir sonucu olarak işletme yönetiminde sorumluluk sahibi olan, işletmenin sahipleri adına yönetimi üstlenen yöneticilere, karşılaşacakları ahlaki seçimler içeren problemlerde yol gösterebilecek davranış standartlarının her birinin, kodlar halinde belirtilip paydaşlarına açıklanmasına yönelik çalışmalar dikkat çekmeye başlamıştır. Bu çalışmalar ile her meslekte etik kodlar oluşturma ihtiyacı doğmuş ve bu yöndeki çabalar artmıştır. Katlanılan vekâlet maliyetlerine rağmen, giderek daha büyük skandalların ortaya çıkması ve yönetim kademelerince zaman zaman tercih edilen etik dışı karar seçeneklerinin yol açtığı zararların önlenmesinde çeşitli önlemler ortaya atılmaktadır. Bu konu ile bağlantılı olarak, kurucu ailenin şirket anayasası doğrultusunda işletme içerisinde ilke haline getirme çabası içerisinde olduğu ve eğitimler, kurallar, yönergeler ortaya koyarak oluşturmaya çalıştığı, sonrasında ise tüm paydaşlarına açıklayarak uymayı taahhüt ettiği etik kodların, bu yönde etkili olup olamayacağı düşünülür ve tartışılır hale gelmiştir.

Corporate managers are the agents of shareholders; however, they have conflicting interests. Agency theory, the analysis of such conflicts, is now a major part of the economics literature. Agency theory is an useful tool for analyzing modern firm which is defined as contractual relations. Agency costs are the results of this relationship. The interest in corporate social responsibility, sustainable business practice, corporate governance, business ethics, integrity and compliance management has grown markedly in the past decade. It is not only stakeholders who expect companies to pay greater attention to values, norms and principles, but also companies themselves are acknowledging the importance of responsible business practice. What are the company’s responsibilities and how can the board and management ensure that the company meets its responsibilities? Despite the agency costs to prevent the further scandals and the loss that is caused by the unethical decisions made by the top managers, various precautions and solutions are suggested. The economists view the corporate ethics problem as a problem of reducing agency costs. According to them, there are different ways to reduce agency costs. One of these ways and the most common one is to use contracts that better align the interests of managers and the employees they supervise with those of shareholders. Examples of such contracts in the companies are executive or employee stock options, bonus plans and also profit sharing arrangements. The other way, which was our target research area, is to raise the ethical standards, so that company managers and employees face higher costs from value-reducing behavior. Higher ethical standards can be expected to lead to lower agency costs, greater corporate efficiency, higher corporate values, and greater social welfare. They also can reduce managerial and employee opportunism, better ethical standards can increase corporate brandname capital and hence shareholder wealth. A much recommended management instrument to achieve this is the “business-or ethical – codes”. At all of the levels of today’s companies – especially at the mid – and top management levels – the ethical codes which had been created towards the ethical philosophy, have a big importance to establish the behavior standards. During the last 25-30 years, ethical behaviour problems became an issue and had been raised in almost every aspect of life, from politics to science, from businesses, to media. Different point of views came up to discussions. This brought sensitivity to the issue of ethics in both private and public sphere. In a result of this, members of board, or top managers who have responsibility to run the business in the name of the company owners, shareholders, have been given a list of ethical codes, which consist of ethical behaviour standards to comply with and share these from top to down. Thanks to increasing number of these studies, a need to form ethical codes in every profession and the efforts are getting higher. Many companies and most professions have written their ethical codes and promise to behave towards this codes. Some companies started educational programs dealing with ethics for their employees. Some companies already established ethics committees and recruit ethical managers. Regarding this issue, code of ethics, that are set by the founder family, are aiming to be adopted as a firm principle and behavior standards through training, rules and directives had been argued whether it will be effective or not. The subject of this study comprises an examination about the effects of ethical codes on agency costs. In this study, 9 board members of turkish publicly held corporations had been interviewed which declared their ethical codes at their web page and asked 13 questios about their companies. This companies are all family companies. Their chairmans of the board are family members. All of these participants who joined to our research, were member of the founder family. Our aim was finding out what they do towards these codes at their companies. Do they believe if these codes will help to reduce their agency costs? According to analysis results; it is seen that there is a positive relation between ethical codes and agency costs, which are supported from the founder family. Their attitudes will be an example for their employees. If this codes turn to a company culture and are protected by themselves carefully, they can help to reduce the agency costs. Otherwise if they just stay as written and shared codes, they can bring additional costs to the companies.
A SURVEY ABOUT THE IMPACT OF ETHICAL CODES ON AGENCY COTS